Technical Note: Histological validation of anatomical imaging for breast modeling using a novel cryo‐microtome. Issue 11 (11th October 2021) - Sen, Anando; Fowlkes, Natalie W.; Kingsley, Charles V.; Kulp, Adam M.; Huynh, Thomas; Willis, Brandy J.; Brewer Savannah, Kari J.; Bordes, Mary Catherine A.; Hwang, Ken‐Pin; McCulloch, Molly M.; Stafford, Roger Jason; Contreras, Alejandro; et al.
Abstract: Purpose: Precise correlation between three‐dimensional (3D) imaging and histology can aid biomechanical modeling of the breast. We develop a framework to register ex vivo images to histology using a novel cryo‐fluorescence tomography (CFT) device. Methods: A formalin‐fixed cadaveric breast specimen, including chest wall, was subjected to high‐resolution magnetic resonance (MR) imaging. The specimen was then frozen and embedded in an optimal cutting temperature (OCT) compound. The OCT block was placed in a CFT device with an overhead camera and 50 μm thick slices were successively shaved off the block. After each shaving, the block‐face was photographed. At select locations including connective/adipose tissue, muscle, skin, and fibroglandular tissue, 20 μm sections were transferred onto cryogenic tape for manual hematoxylin and eosin staining, histological assessment, and image capture. A 3D white‐light image was automatically reconstructed from the photographs by aligning fiducial markers embedded in the OCT block. The 3D MR image, 3D white‐light image, and photomicrographs were rigidly registered. Target registration errors (TREs) were computed based on 10 pairs of points marked at fibroglandular intersections. The overall MR‐histology registration was used to compare the MR intensities at tissue extraction sites with a one‐way analysis of variance. Results: The MR image to CFT‐captured white‐light image registration achieved a mean TRE of 0.73 ± 0.25 mm (less than the 1 mm MR slice resolution). The block‐face white‐light image and block‐face photomicrograph registration showed visually indistinguishable alignment of anatomical structures and tissue boundaries. The MR intensities at the four tissue sites identified from histology differed significantly ( p  < 0.01). Each tissue pair, except the skin‐connective/adipose tissue pair, also had significantly different MR intensities ( p  < 0.01). Conclusions: Fine sectioning in a highly controlled imaging/sectioning environment enables accurate registration between the MR image and histology. Statistically significant differences in MR signal intensities between histological tissues are indicators for the specificity of correlation between MRI and histology.